ASSOCIATION BETWEEN DANCE PRACTICE AND LEVELS OF ANXIETY AND STRESS IN YOUNG UNIVERSITY STUDENTS (REMUNOM, 2024)
Introduction: Adolescence is the phase in which decision-making is necessary, making it a risky transition, as young people can end up compromising their physical and mental health. When entering university, students end up following a routine of great challenges and exhaustion, which can generate depression, stress and anxiety. Objective: Therefore, the study aimed to associate dance practice with anxiety and stress levels in young university students. Method: The research is a field study with a quantitative approach, taking place at a university located in the city of Juazeiro do Norte-CE. The EADS-21 Anxiety, Depression and Stress Scale was used.  Data analyzes were performed using the JAMOVI software program version 1.6, the Shapiro Wilk test and the chi-square test. 22 young women, between 17 and 27 years old, participated in Nursing, Dentistry, Law, Physiotherapy, Veterinary Medicine and Psychology courses, divided between those who practiced dancing and those who were sedentary. Results: Participants who practiced dancing had a lower level of stress, depression and anxiety, whereas sedentary people had a percentage of 50% in mild stress, 50% in moderate stress, 100% in moderate depression, 66.7% in moderate anxiety and 33.3% in severe anxiety. Conclusion: It is concluded that dancing is a very important aerobic activity for reducing stress, anxiety and depression.